199k views
0 votes
Factor completely. x2−5x−36 Enter your answer in the box.

User MacGucky
by
5.5k points

2 Answers

5 votes

Answer:

x^2 − 5x − 36 = (x - 9)(x + 4)

Explanation:

You need to find two numbers whose product is -36 and whose sum is -5.

-36 = -4 * 9; sum -4 + 9 = 4 wrong sum

-36 = -9 * 4; sum -9 + 4 = -5 right sum

The numbers are -9 and 4.

Answer: x^2 − 5x − 36 = (x - 9)(x + 4)

User Messerbill
by
6.6k points
1 vote

Answer:

(x - 9)(x + 4)

Explanation:

x^2−5x−36

As you know, -36 = -9 * 4 and (-9) + 4 = -5

so Factor

= (x - 9)(x + 4)

User Herrmarek
by
6.3k points